Balance Sheet Network Analysis of Too-Connected-to-Fail Risk in Global and Domestic Banking Systems - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2010)
The 2008/9 financial crisis highlighted the importance of evaluating vulnerabilities owing to interconnectedness, or Too-Connected-to-Fail risk, among financial institutions for country monitoring, financial surveillance, investment analysis and risk management purposes. This paper illustrates the use of balance sheet-based network analysis to evaluate interconnectedness risk, under extreme adverse scenarios, in banking systems in mature and emerging market countries, and between individual banks in Chile, an advanced emerging market economy.